2017
DOI: 10.1002/ajpa.23145
|View full text |Cite
|
Sign up to set email alerts
|

Primates on display: Potential disease consequences beyond bushmeat

Abstract: Human interactions with nonhuman primates vary tremendously, from daily cultural engagements and food commodities, to pet ownership and tourist encounters. These interactions provide opportunities for the exchange of pathogenic organisms (both zoonoses and anthroponoses). As exposures are not limited to areas where bushmeat usage continues to be a major problem, we must work to understand better our motivations for engaging in activities like owning primates as pets and having direct physical contact with wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 122 publications
1
17
0
Order By: Relevance
“…Outside of their natural environment, they can be found in zoological, rehabilitation, or research centers, and even in urban and rural environments. Additionally, these animals exhibit a niche overlap with humans in the case of semi-wild areas ( Muehlenbein, 2017 ). Since the natural habitats of primates are forests, most interactions between humans and primates occur in this high-risk interface.…”
Section: Introductionmentioning
confidence: 99%
“…Outside of their natural environment, they can be found in zoological, rehabilitation, or research centers, and even in urban and rural environments. Additionally, these animals exhibit a niche overlap with humans in the case of semi-wild areas ( Muehlenbein, 2017 ). Since the natural habitats of primates are forests, most interactions between humans and primates occur in this high-risk interface.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one of the main causative agents of human malaria, Plasmodium falciparum, once thought to have co-evolved with humans, actually arose from a recent zoonotic transmission from a western gorilla (Gorilla gorilla (Savage, 1847)) [19][20][21] . Nowhere are such risks more evident than in zoological and sanctuary settings, where captive and semicaptive primates come into frequent close contact with people 22,23 . For example, contact with New World primates led to simian foamy virus transmission to primate workers in Brazil 24 and monkeypox virus transmission occurred in staff at a primate sanctuary following a monkeypox outbreak in sanctuary chimpanzees (Pan troglodytes (Blumenbach, 1775)) in Cameroon 25 .…”
mentioning
confidence: 99%
“…Overall, we found that contact is deployed in multiple and inconsistent ways. Contact can be qualified as ''direct,'' that is, a physical exposure to bodily fluids of an infected animal through mucosal or wound exposure; however, this same ''direct contact'' can also refer to aerosolized contact with droplets of infected bodily fluids (Mossoun et al 2017;Muehlenbein 2017;Kurpiers et al 2016;Gilardi et al 2015;Köndgen et al 2008). It can be defined as ''indirect'' or ''secondary,'' ranging from exposure to fomites, feces or vectors to inhabiting the same geographical zone (Kurpiers et al 2016;Gilardi et al 2015;Ravasi et al 2012;Davies and Pedersen 2008;Wolfe et al 2007).…”
Section: Contact and Exposurementioning
confidence: 99%